Economic Entity Concept, Penata Keuangan dan Aplikasi Lamikro Era Industri 4.0 (UMKM Provinsi Kepulauan Bangka Belitung) - Wawan Irawan; Rulyanti Susi Wardhani (Universitas Kristen Maranatha, 2021)
This study aims to determine the importance of Financial Arrangement, Entity Concept, and Lamikro Application in Micro, Small, and Medium Enterprises (MSMEs) in Bangka Belitung Province. The data analysis technique used in this study is to use Importance Performance Analysis (IPA), which describes the condition of MSMEs in Bangka Belitung Province regarding aspects of financial arrangement, entity concept, and technology the use of the Lamikro application. The results show that MSMEs in Bangka Belitung Islands Province in managing finances still use manuals. Still, some are using applications to consider it not a priority or important in managing finances. Furthermore, the economic entity concept and Lamikro application are still lacking in use, so they are still considered more important and priority in supporting MSMEs' performance in the Province of Bangka Belitung Islands. Keywords: Financial Structuring, Entity Concept (Economic Entity Concept), Lamikro Application